2017
DOI: 10.1038/srep46417
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of physical frailty: Latent class analysis and associations with clinical characteristics and outcomes

Abstract: Frailty is a well-recognized geriatric syndrome with various definitions and conceptual frameworks. This study aimed to use latent class analysis to discover potential subtypes of pre-frail and frail older people. Data from the I-Lan Longitudinal Aging Study (ILAS), a community-based cohort study was used for analysis. Latent class analysis was applied to characterize classes or subgroups with different frailty phenotypes among ILAS participants targeting older adults aged 65 and above, capable of completing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 54 publications
5
56
1
1
Order By: Relevance
“…28 They might present as mobility-type frailty, which are the core determinants of physical frailty and sarcopenia as well as significant predictors of adverse clinical outcomes. 7,[29][30][31] Recent research has recommended using weakness and slowness as diagnostic criteria of cognitive frailty. 32,33 The current results also suggest the importance of weakness and slowness in relation to changes in brain structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 They might present as mobility-type frailty, which are the core determinants of physical frailty and sarcopenia as well as significant predictors of adverse clinical outcomes. 7,[29][30][31] Recent research has recommended using weakness and slowness as diagnostic criteria of cognitive frailty. 32,33 The current results also suggest the importance of weakness and slowness in relation to changes in brain structures.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this analysis indicated that the association of weakness and slowness with the brain volume was more significant when both weakness and slowness was observed than either weakness or slowness (Supplementary Figure 5). Therefore, mobility-type frailty 29 might be most closely associated with regional brain volumes.…”
Section: Discussionmentioning
confidence: 99%
“…7 This condition is associated with mortality in patients with end-stage liver disease. 8 Early diagnosis and prevention of osteoporosis is needed in CLD patients.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report proposed that physical frailty may be classified into mobility and non-mobility subtypes, and differences in clinical characteristics and mortality between frailty subtypes have been clearly shown. 19 Moreover, mobility subtype frailty is associated with cognitive declines in non-memory domains, mainly executive function. 20,21 Brain imaging of the same cohort revealed significantly reduced cerebellar gray matter among pre-frail and frail older adults, 22 especially those with mobility subtype frailty.…”
Section: Amentioning
confidence: 99%